Ukrainian Society under Conditions of Total Anomy - Сальнікова, Світлана Анатоліївна; Salnikova, Svitlana A. (Centre of Sociological Research (Ukraine), 2014)
The presence of specific phenomena of post-soviet anomy such as the criminalization of judicial and legal system, «state capture», double institutionalization and others aggravates the condition of social disorganization of Ukrainian society. Determination of the degree of influence of anomy on society as a whole and on selected groups is the main goal of this study. The author has used a technique construction of Index of Anomic Demoralization, Cynicism Index, and two Indexes of Social Well-being on the datasets of national surveys (1992–2012) of the Institute of Sociology of the National Academy of Sciences of Ukraine. All indexes for the entire period are quite high and they indicate the total anomy of Ukrainian society. After having analyzed the indicators of anomy in regional, age and sex, and professional and labour aspects, the author came to the following conclusions: (1) indications of anomy and cynicism are aggravated from the West to the East of the country, while the inhabitants of the Southwest and Kyiv feel less demoralized; inhabitants of the South-eastern part of Ukraine – are more demoralized; social well-being of the rural population is significantly worse than that of the inhabitants of large cities; (2) age differences as an indicator of generational change are more significant than regional, it signifies the integrity of the Ukrainian society; (3) professional and labour Ukrainians’ differences according to indicators of anomy and cynicism are the most significant. The results confirm the need to reform public institutions, the involvement of professionals in all spheres of public life.
Keywords: indicators of anomy; Index of Anomic Demoralization; Cynicism Index; Index of Social Well-being